Use of nucleic acid recognition methods (m-PCR and RT-LAMP) for the detection of foot-and-mouth disease virus excreted in cow milk - RANJAN, RAJEEV; BISWAL, JITENDRA KUMAR; SHARMA, GAURAV KUMAR; SHARMA, AJAY KUMAR; SINGH, KARAM PAL; MISRI, JYOTI; PATTNAIK, BRAMHADEV (The Indian Journal of Animal Sciences, 2016)
The present study was undertaken to see the excretion of FMD virus in milk during and after the subset of FMD outbreak. Fore-milk (50 ml) was sampled from 12 clinically infected and 3 asymptomatic cows in the morning. Analytical sensitivity of NAR methods was estimated using uninfected negative milk sample spiked with 105.7 TCID50/ml FMD serotype O virus (IND R2/1975) in 10 fold serial dilution. Detection limit of mPCR and RT- LAMP assay was 102.7 and 101.7 TCID50/ml, respectively. 15 individual and pooled cows’ milk samples infected with FMD virus were processed for virus isolation (VI) and detection till 37 days post clinical manifestation (dpm). Virus isolation from individual and pooled milk from infected cow was positive till 6 and 4 dpm, respectively. Individual milk and pooled milk samples were found positive by m-PCR till 37 and 14 dpm, respectively, but by RT-LAMP till 37 and 21 dpm, respectively. In case of asymptomatic cows, viral genome was detected 2–5 days before appearance of disease in other animals. Milk virus isolate had 100% nucleotide identity at VP1 coding region. mPCR and RT LAMP assays has potential to detect FMD virus in milk and help to prevent the spread of FMD virus from one place to another place.